Improved water and soil management: the key to future food security - Chartres, Colin J. (2010)
Growing global population and a combination of dietary change, biofuels production, urban and industrial water demand and climate change will see food crises becoming more frequent in the next 40 years. Food and feed production must double to feed 9.1 billion people in 2050. This will require using twice as much water as at present or increasing water productivity. It is argued that we need a Blue-Green revolution to deliver water productivity increases. This revolution will depend on increases of both rainfed and irrigated production and has to include improvements in soil fertility and institutional and governance of agriculture and natural resources.